Healthcare providers insights on the Baby-Friendly Hospital Initiative: A cross-sectional study in Qatar - Jussara D. S. Brito (22556090) (2025)
Introduction The Baby-Friendly Hospital Initiative (BFHI) by WHO and UNICEF promotes exclusive breastfeeding and enhances maternal and child health. Introduced in Qatar in 2016, its accreditation and implementation remain incomplete. This study evaluates the knowledge, attitudes, and practices (KAP) of clinical staff regarding BFHI at Al-Wakra Hospital. Methods A cross-sectional study was conducted among clinical staff in Obstetrics, Gynecology, and Pediatrics at Al-Wakra Hospital, using a convenience sampling method from April 2022 to January 2023. An online questionnaire based on the WHO/UNICEF Competency Verification Toolkit gathered data on sociodemographic, WHO BFHI course participation, and KAP levels. Statistical analysis was performed using t-tests and ANOVA in STATA 17.0, with significance at p<0.05. Results The study involved 141 participants, predominantly female (87.2%) with an average age of 38.4 years; most were nurses (85.1%). Knowledge scores were higher in males (8.0 ± 1.3) than females (7.1 ± 1.8, p=0.051), and specialists scored better than nurses (8.0 ± 1.4 vs 7.1 ± 1.8, p=0.033). A weak correlation was found between age and KAP scores. Conclusions The study highlights the need for continued BFHI education, especially for head nurses and midwives, to enhance implementation and ensure consistent competency among healthcare professionals. Other Information Published in: European Journal of Midwifery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.18332/ejm/203687